Supply Chain and Logistics Management / Fourth Edition - Bixby Cooper M.; Bowerson Donald J; Bowersox John C; Closs David J (Mc Graw Hill, 2013)
Preface, Supply Chain Logistics Management, 21st Century Supply Chains, Logistics, Customer Relationship Management, Procurement, Manufacturing, Integrated Operations Planning, Supply Chain Logistics Operations, Inventory, Transportation, Warehousing, Packaging and Handling, Supply Chain Logistics Design, Global Supply Chains, Network Design, Operations Analysis, Supply Chain Logistics Administration, Collaboration, Performance Measurement, Risk and Sustainability, Epilogue, Problems, Cases, Index.